P156 NAEDI lung cancer awareness campaign in London. (2nd December 2011) - Safa, A; Berry, A; Ali, H; Car, J; Bowen, E F
Abstract : Background: Lung cancer is the leading cause of cancer mortality in the UK. Survival rates over the last 30 years have not significantly improved. The NAEDI initiative is working to promote early diagnosis to improve stage at presentation and increase survival rates. Objectives: The project in Hammersmith & Fulham focused on the three most deprived wards, population 32 000). The aims were to increase public awareness and intention to act on symptoms by 10%, GP chest x-ray referrals by 15%, and Two Week Rule (TWR) referrals and, ultimately, earlier stage at diagnosis by 10%. Methods: Nine general practices in the target area received educational seminars on NICE guidelines, project details and aims. 40 pharmacies, 25 smoking cessation advisors and 30 district nurses received education on symptoms, communication and management skills, and were provided with campaign materials. The public campaign involved training 42 health champions in key messages regarding alarm symptoms. Face-to-face contact was made with 1300 people. Local advertising had an estimated reach of three million people. The campaign ran from February to July 2011. Results: Data on public perceptions were collected with a validated form of the Cancer Awareness Measure. On average there was a 12% increase in unprompted recall of the commonest lung cancer symptoms, and a 26% increase in intention to make urgent GP contact for such symptoms. Data from the 9 practices during the campaign period in 2011 compared to the same period in 2010 showed a rise in chest x-ray referrals from 350 to 463 (32% increase). In 2010 there were no TWR referrals and seven lung cancer diagnoses. For 2011, there was 1 TWR referral (lung cancer) and 10 new lung cancers diagnosed. Conclusions: Community engagement has been a success locally with active involvement of trained champions into future public health work streams. Data collection again next year is required to evaluate whether the increase in chest x-ray referral rates is maintained and translated into earlier stage at diagnoses. The success of primary care engagement needs roll out across the borough and embedding into future service provision to ensure sustainability.